Statistical Analysis of the Most Influential Cryptocurrencies (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
A comparison of the most 30 influential cryptocurrencies has been made, based on the "CoinMarketCap" web page. Over the last few years, an increasing number of the world's population is investing in the cryptocurrency market. The emphasis is placed on Bitcoin, which is the absolute leader on this market. The difference between electronic money and virtual currency is explained, followed by the history of crypto values. Finally, the statistical analysis of the most influential cryptocurrencies, during the last year, will be presented.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.